Osteomyelitis and Arthritis by Atypical Mycobacteria in Children: Three Cases - Aquino, Joana; Lemos, Sónia; Balacó, Inês; Matos, Gabriel; Rocha, Graça; Salgado, Manuel (Journal of Pediatric Infectious Diseases, 2019)
Introduction Osteoarticular infections caused by atypical mycobacteria are uncommon, with osteitis being more common and arthritis being rare. We describe two cases of subacute osteomyelitis and one of chronic osteomyelitis with arthritis. Case Reports Three boys, aged between 7 and 20 months. Clinical presentations: case 1—swelling of right forearm; case 2—limping and swelling of right hallux; case 3—pain and restriction of motion of right lower limb with effusion. None had fever. All had received Bacillus Calmette–Guérin (BCG) and none had contact with tuberculosis. All had thrombocytosis, and erythrocyte sedimentation rate was between 17 and 44 mm/1st hour. All had osteolytic lesions on X-ray with a sclerotic halo and swelling of the surrounding soft tissues, and invasion of the metaphysis and/or epiphysis. Bone histopathological studies revealed granulomatous inflammation or epithelioid cells in all cases. Microbiological identification was positive by culture in one case (Mycobacterium bovis) and by polymerase chain reaction in two cases (Mycobacterium spp. and M. avium). Immunodeficiency screening was negative in all cases. All were treated with antituberculous agents and made good clinical and radiological recoveries. Discussion Osteolytic lesions should raise suspicion of mycobacterial infection, including BCG vaccine, particularly in the presence of granulomatous inflammation. The prognosis was favorable in all patients. Although immune deficits were not identified in any of our three patients, it should be routinely tested for in such cases.
Keywords: BCG; osteitis; subacute osteomyelitis; chronic osteomyelitis; mycobacteria